Cryoballoon ablation of left atrial roof with a novel cryoballoon system. (3rd October 2022) - Shigeta, T; Yamauchi, Y; Oda, A; Sudo, K; Arai, H; Sagawa, Y; Okishige, K; Goya, M; Sasano, T
Abstract: Introduction: A novel cryoballoon system (POLARx) has emerged and its efficacy regarding pulmonary vein isolation (PVI) has been already investigated. On the other hand, cryoballoon ablation of left atrial (LA) roof has been performed using a conventional cryoballoon system (Arctic Front Advance Pro [AFA-Pro]) in addition to PVI. However, cryoballoon ablation of LA roof with POLARx has not been investigated yet. Methods: We performed cryoballoon ablation of LA roof with POLARx in 22 patients after we achieved PVI. After the cryoballoon ablation, complete conduction block at LA roof and isolation of all PVs were confirmed by creating an activation map during high right atrium pacing. If they could not be obtained with solely a cryoballoon, touch up ablation with radiofrequency ablation was permitted. The procedural data during ablation with POLARx was compared with those during ablation with AFA-Pro we had performed in a historical cohort of patients (n=46). Results: Complete conduction block at LA roof without touch up ablation could be obtained in all the patients in POLARx group and 44 (95.7%) patients in AFA-Pro group. Total procedure time was almost similar in both groups (164.2±35.4 min for POLARx vs 180.3±35.4 min for AFA-Pro, p=0.10). During LA roof line ablation, nadir balloon temperature was significantly lower in POLARx group (right side: −53.6±4.4°C for POLARx vs −45.6±4.6°C for AFA-Pro, p<0.01, central part: −56.4±4.3°C for POLARx vs −46.0±3.7°C for AFA-Pro, p<0.01, left side: −55.1±3.5°C for POLARx vs −45.7±5.3°C for AFA-Pro, p<0.01), and balloon temperature reached −40°C earlier in POLARx (right side: 30.7±8.9 sec for POLARx vs 78.0±39.8 sec for AFA-Pro, p<0.01, central part: 30.6±9.3 sec for POLARx vs 65.9±33.3 sec for AFA-Pro, p<0.01, left side: 30.4±4.2 sec for POLARx vs 78.8±49.6 sec for AFA-Pro, p<0.01). Total freezing time required for LA roof line ablation was significantly shorter in POLARx group (589.3±163.6 sec for POLARx vs 877.5±191.7 sec for AFA-Pro, p<0.01).The scar area created after LA roof line ablation was similar in both groups (9.3±4.1 cm 2 for POLARx vs 11.0±4.8 cm 2 for AFA-Pro, p=0.23). Conclusion: Complete conduction block at LA roof could be obtained after cryoballoon ablation with POLARx, in the same way as AFA-Pro. Lower nadir balloon temperature could be expected in shorter freezing time during LA roof line ablation in using POLARx compared with AFA-Pro. Funding Acknowledgement: Type of funding sources: None.